2011
DOI: 10.1021/cg100951y
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization of a Force Field for Te−N Secondary Bonding Interactions and Its Application in the Design of Supramolecular Structures Based on Heterocyclic Building Blocks

Abstract: 1,2,5-Telluradiazole rings have a remarkably strong tendency toward association through Te-N secondary bonding interactions in the solid state. The reproducibility of the bond lengths and angles in the known crystal structures allowed the parametrization of an anharmonic force field to accommodate both the inter-and intramolecular Te-N bonds. The new parameters were tested against published crystal structures and were able to accurately reproduce the experimentally observed geometries. The incorporation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…As described recently by Ta ylor and co-workers, [21] it is well accepted that an estimation of the ability to make X···Y SBIs can be obtainedc onsidering the magnitude of V s,max at Xa nd Y atoms (i.e.,t he value of the electrostatic potential at the point of the highest charge for both donor and acceptor atoms), [21][22][23][24][25][26][27] althought he chalcogenb onding interactions cannotb ec onsidered as purely electrostatic interactions. [34][35][36][37][38] Calculations have been firstly performed on non-substituted benzo-1,3-chalcogenazoles using Gaussian 09 including the D01 Revision, with the B97-D3/Def2-TZVP level of theory. [21] After geometry optimization, the ESPs were mapped on the van der Waals surface of each molecule up to an electron density of 0.001 electron bohr À3 .…”
Section: Resultsmentioning
confidence: 99%
“…As described recently by Ta ylor and co-workers, [21] it is well accepted that an estimation of the ability to make X···Y SBIs can be obtainedc onsidering the magnitude of V s,max at Xa nd Y atoms (i.e.,t he value of the electrostatic potential at the point of the highest charge for both donor and acceptor atoms), [21][22][23][24][25][26][27] althought he chalcogenb onding interactions cannotb ec onsidered as purely electrostatic interactions. [34][35][36][37][38] Calculations have been firstly performed on non-substituted benzo-1,3-chalcogenazoles using Gaussian 09 including the D01 Revision, with the B97-D3/Def2-TZVP level of theory. [21] After geometry optimization, the ESPs were mapped on the van der Waals surface of each molecule up to an electron density of 0.001 electron bohr À3 .…”
Section: Resultsmentioning
confidence: 99%
“…[90] Twelve of the fourteen asymmetricm onomers align to orient their largest substituent anti-r elative to each other,r egardlesso ft he substituent being electron withdrawing or donating ( Figure 6). [91] For instance, in 2d [92] and 2e [92] the 4-NH 2 and 4-NO 2 groups differ dramatically in their electronic properties but 2d and 2e contain nearly identical squares (2d; 2e, respectively:C B ave = 3.12 ;3 .09 , q ave = 72.78;7 4.98, f ave = 0.08;0.08, F ave = 177.08;1 77.28).…”
Section: The 2s-2n Squarec Lass Assembled By Chalcogen Bondingmentioning
confidence: 99%
“…Hybrid DFT (B3LYP/6-31G(d,p), SDB-cc-pVTZ for Te) showed that the dimers of the cations 40 and 41 are minima in the potential energy surface but the overall intermolecular interactions would be repulsive in gas phase; favourable binding energies are obtained only after inclusion of the dielectric properties of the medium (acetonitrile) modeled by the Polarized Continuum Model: −53.5 for 40 and −22 kJ/mol for 41 [68,69]. Meticulous DFT mapping of the potential energy surface by distortion of the [Te-N] 2 supramolecular synthon [15] has been used to parameterize a force field for the design of new supramolecular assemblies [73]. Steric effects on the formation of the synthon have also been examined [66].…”
Section: [Te-m-d]mentioning
confidence: 99%